Penajaman Kualitas Citra Digital Menggunakan Histogram Equalization - Herdy Kurnia; Taufik Hidayat (STMIK Triguna Dharma, 2023)
CCTV (Closed-circuit Television) is a surveillance camera that is installed on roads and in various rooms around the world with the aim of reducing crime and increasing public safety. Often, the image quality of CCTV has poor results, one of the causes is noise. This condition causes the information contained is sometimes not well conveyed. Image enhancement is a part of image processing which has the aim of improving image quality by manipulating image parameters. The application of this research is to sharpen the quality of screen capture on CCTV. The method applied is histogram equalization which can improve image quality. Histogram equalization method will be applied using Google Colab because its use has good portability.